Student's attitude towards learning music / Syazwan Hakim Amirul Ihsan - Amirul Ihsan, Syazwan Hakim (2013)
Attitude is the favorable or unfavorable perceptions towards something. Attitudes are generally positive or negative thought and perception towards people, place or event. People may have conflicting attitudes or feelings towards an object, which can simultaneously be both positive and negative towards the task or activity. According to Hogg and Vaughn, attitude is a relatively enduring organization of beliefs, feelings and behavioral tendencies towards socially significant objects, groups, events or symbols (Hogg & Vaughan 2005, p. 150). Attitude also defined by Zimbardo as a positive or negative evaluation of people, objects, event, activities, ideas, or anything in our environment (Zimbardo, 1999). Meanwhile, other opinion says that attitude is the relatively stable evident behavior of a person which affects his status (Bain, 1993). Based on another opinion by Lumley, attitude is a susceptibility to certain kinds of stimuli and readiness to respond repeatedly in a given way (Lumley, 1928). All the definition of the attitude achieved shows that the attitude involved in psychological area that need to be study in deep. Attitude is an important element in many field of life. Attitude may affect the person behavior or perspective towards something. As it goes towards learning process, attitude act as an agent so that the learning process is achievable and productive.